2020
DOI: 10.1126/scitranslmed.aav7431
|View full text |Cite|
|
Sign up to set email alerts
|

Dendritic cells dictate responses to PD-L1 blockade cancer immunotherapy

Abstract: PD-L1/PD-1 blocking antibodies have demonstrated therapeutic efficacy across a range of human cancers. Extending this benefit to a greater number of patients, however, will require a better understanding of how these therapies instigate anticancer immunity. Although the PD-L1/PD-1 axis is typically associated with T cell function, we demonstrate here that dendritic cells (DCs) are an important target of PD-L1 blocking antibody. PD-L1 binds two receptors, PD-1 and B7.1 (CD80). PD-L1 is expressed much more abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
200
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(224 citation statements)
references
References 29 publications
7
200
0
Order By: Relevance
“…Thus, we can speculate that the addition of anti-PDL2 Ab to anti-PDL1 therapy soon after immunogenic chemotherapy maximizes the ability of CD103 + DCs to cross-present tumor antigens by shielding two non-redundant immunoinhibitory signals, ultimately leading to an efficient and long-lasting CD8 + T cell stimulation. Along these lines, Mayoux and colleagues have recently shown that blocking PDL1 on DCs allow a better stimulation of T cell priming with positive immunological and likely clinical consequences for checkpoint blockade therapy in cancer patients [43]. In addition to CD103 + DCs, intratumoral recruitment of eosinophils may contribute to tumor rejection through both direct cytotoxicity towards tumor cells and by secreting chemokines capable of attracting CD8 + T cells as recently reported [20,44,45].…”
Section: Discussionmentioning
confidence: 93%
“…Thus, we can speculate that the addition of anti-PDL2 Ab to anti-PDL1 therapy soon after immunogenic chemotherapy maximizes the ability of CD103 + DCs to cross-present tumor antigens by shielding two non-redundant immunoinhibitory signals, ultimately leading to an efficient and long-lasting CD8 + T cell stimulation. Along these lines, Mayoux and colleagues have recently shown that blocking PDL1 on DCs allow a better stimulation of T cell priming with positive immunological and likely clinical consequences for checkpoint blockade therapy in cancer patients [43]. In addition to CD103 + DCs, intratumoral recruitment of eosinophils may contribute to tumor rejection through both direct cytotoxicity towards tumor cells and by secreting chemokines capable of attracting CD8 + T cells as recently reported [20,44,45].…”
Section: Discussionmentioning
confidence: 93%
“…Within the solid tumor microenvironment, PD-L1 can be expressed on many cells of hematopoietic origin, often collectively referred to as “immune infiltrate”, including dendritic cells [ 17 ], tumor-associated macrophages (TAMs) [ 4 , 18 ], myeloid-derived suppressor cells (MDSCs) [ 19 ] and T-cells [ 3 ]. PD-L1 can also be expressed on the non-hematopoietic stromal elements, principally the endothelial cells of the tumor vasculature [ 20 ] and cancer-associated fibroblasts [ 21 ].…”
Section: Pd-l1 Expression On Non-tumor Cellsmentioning
confidence: 99%
“…PD-L1 expressed on DCs provides a direct T-cell inhibitory input via PD-1 but also helps override T-cell activation in the context of antigen recognition [ 17 , 25 ]. PD-L1 has two binding partners, the inhibitory receptor PD-1 on T-cells and the co-stimulatory molecule CD80 (B7.1) on antigen-presenting cells.…”
Section: Pd-l1 Expression On Non-tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides tumor cells, PD-L1 is also expressed in various types of cells, including activated T cells, NK cells, dendritic cells (DC) and myeloid-derived suppressor cells (MDSCs) [49,[51][52][53][54]. In this study, we preliminarily veri ed the feasibility and e cacy of CAR-T cells targeting PD-L1 for the treatment of solid tumors, and we found that PD-L1 was up-regulated in T cells that were activated through either endogenous TCR or CAR signaling, making these activated T cells be the target of anti-PD-L1 T cells.…”
Section: Discussionmentioning
confidence: 99%